Enhancing the Dyeability of Polypropylene Fibers by Melt Blending with Polyethylene Terephthalate - Fereshteh Mirjalili; Siamak Moradian; Farhad Ameri (The Scientific World Journal)
Attempts were made to modify polypropylene fibers by melt blending with polyethylene terephthalate in order to enhance the dyeability of the resultant fiber. Five blends of polypropylene/polyethylene terephthalate/compatibilizer were prepared and subsequently spun into fibers. Three disperse dyes were used to dye such modified fibers at boiling and 130°C. The dyeing performance of the blend fibers, as well as the morphological, chemical, thermal, and mechanical properties, of the corresponding blends was characterized by means of spectrophotometry, polarized optical microscopy, scanning electron microscopy (SEM), FT-IR spectroscopy, differential scanning calorimetry (DSC), and tensile testing.